A Novel Method to Assess Subject‐Specific Architecture of the Achilles Tendon In Vivo in Humans - Finni, Taija; Khair, Raad; Franz, Jason R.; Sukanen, Maria; Cronin, Neil; Cone, Stephanie (Scandinavian journal of medicine & science in sports, 2025)
ABSTRACT The Achilles tendon (AT) comprises three subtendons whose relative locations, and respective lines of action, vary individually. This study was aimed to demonstrate the efficacy of a novel method, combining Ultrasound and electrical STIMulation (USTIM), to identify the in vivo location of individual subtendons in cross‐sections of the AT. We individually stimulated the triceps surae muscle heads and imaged localized tissue movement on a transverse plane 1 cm proximal to the calcaneus using B‐mode ultrasonography. Movement induced by muscle stimulation was presumed to arise from movement in the respective subtendon. Frame‐by‐frame changes in grayscale values were analyzed to detect localized tissue movement, establishing the three subtendon locations. From 12 successfully assessed legs, we found test–retest reliability to be excellent (ICC = 0.93, N = 3), and intra‐ and inter‐rater reliability to be good for the subtendon centroid locations (ICC > 0.77, N = 12). Reliability for identifying the subtendon area was good for test–retest (ICC = 0.77) and intra‐rater assessments (ICC > 0.70) but moderate between raters (ICC = 0.53). Subtendon centroid locations assessed using USTIM showed a strong association (N = 2; r2= 0.80, p < 0.001) with those identified via the high‐field MRI method established by Cone et al. Fitting with prior literature, the majority of (83%) tendons were identified as low twist type I. The novel USTIM method can identify in vivo locations of the three subtendons within a cross‐section of AT with moderate to excellent reliability. This method could be used to unravel the intricacies of structure–function relationships in the AT, with potential clinical benefits for treatment of patients with AT injuries.